2016
DOI: 10.1016/j.erss.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

What drives the development of community energy in Europe? The case of wind power cooperatives

Abstract: Abstract:The dominant model of energy infrastructure has historically been conceived in a very centralized fashion, i.e. with hardly any citizen involvement in energy generation. Yet, increasing attention is being paid to the transition process towards a more decentralized configuration. This article examines the factors likely to foster citizen and community participation as regards wind power cooperatives in Denmark, Germany, Belgium and the UK. Using Elinor Ostrom's Social-Ecological System Framework, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
212
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 350 publications
(240 citation statements)
references
References 36 publications
3
212
0
5
Order By: Relevance
“…Indeed, it has been argued that the participation of citizens in benefits and decision-making processes of RE projects may increase levels of societal acceptability of renewables, especially in the case of onshore (Bauwens, 2015;Maruyama et al, 2007) and offshore wind farms (Walker et al, 2014). Comparative research has shown that a high degree of citizen involvement in wind energy projects is positively correlated with high deployment rates (Bauwens et al, 2016;Toke et al, 2008). In the same perspective, while Mumford and Gray (2010) show evidence of a lack of trust from the public in conventional energy actors as far as the deployment of alternative energy in the UK is concerned, the implementation of decentralised RE installations need to be steered by trustworthy individuals and organisations rooted in local communities (Eyre, 2013;Walker et al, 2010).…”
Section: The Roles Of Community-based Initiatives In Speeding Up the mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been argued that the participation of citizens in benefits and decision-making processes of RE projects may increase levels of societal acceptability of renewables, especially in the case of onshore (Bauwens, 2015;Maruyama et al, 2007) and offshore wind farms (Walker et al, 2014). Comparative research has shown that a high degree of citizen involvement in wind energy projects is positively correlated with high deployment rates (Bauwens et al, 2016;Toke et al, 2008). In the same perspective, while Mumford and Gray (2010) show evidence of a lack of trust from the public in conventional energy actors as far as the deployment of alternative energy in the UK is concerned, the implementation of decentralised RE installations need to be steered by trustworthy individuals and organisations rooted in local communities (Eyre, 2013;Walker et al, 2010).…”
Section: The Roles Of Community-based Initiatives In Speeding Up the mentioning
confidence: 99%
“…CRE initiatives have substantially contributed to RE deployment in several countries. In Denmark, over 150,000 households contributed to wind power financing as members of wind power cooperatives in 2002, and more than 80% of the installed wind turbines were owned by wind power cooperatives and single owners (Bauwens et al, 2016). Similarly, 46% of the total installed RE capacity in Germany in 2012 was owned by individuals, farmers or CRE initiatives (trend:research Gmb and Leuphana Universität; Yildiz et al, 2015).…”
Section: The Roles Of Community-based Initiatives In Speeding Up the mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies explore individual motivations for participating in community energy initiatives [7,25,28]. Others investigate the impacts of structural factors, e.g., policies, on the success of community energy activities [1,3,29,30]. Although it is important to examine the impacts of individual factors on community energy initiatives, community energy also needs to be explored from a more comprehensive context because its success is context-dependent.…”
Section: Internal and External Context Related To Communities For Enementioning
confidence: 99%
“…Recent studies argue for framing energy systems as SESs (Hodbod and Adger 2014;Bauwens et al 2016). Production, distribution and consumption activities within energy systems involve interactions between, on the one hand, ecological processes and technological artefacts and, on the other, social practices and systems of institutional rules.…”
Section: Energy Systems As Social-ecological Systemsmentioning
confidence: 99%